PERAN MUHAMMAD ABDUH DAN KH. MUHAMMAD HASYIM DALAM REFORMASI PENDIDIKAN ISLAM: SEBUAH TINJAUAN PERBANDINGAN - Ma'had, M. Khairin (Mozaic: Islamic Studies Journal, 2024)
Social change that occurs in society is often related to the dynamics of life, which requires reforms in various sectors, one of which is Islamic education. This article discusses the role of two key figures in the reform of Islamic education, namely Muhammad Abduh and KH. Wahid Hasyim, who made significant contributions to the modernization of education in the Islamic world. This research uses a qualitative method with a comparative approach to analyze the thoughts and contributions of both figures. The research findings indicate that despite their different social backgrounds and contexts, both Abduh and Wahid Hasyim share similarities in integrating religious education with general knowledge. Abduh introduced the integration of religious knowledge and science at Al-Azhar University, while Wahid Hasyim adopted a curriculum that combines religious education with scientific subjects at the pesantren. Their contributions to the reform of Islamic education remain relevant to this day, emphasizing the importance of education oriented towards the development of moral, intellectual, and practical skills necessary to face the challenges of the modern era.